Role of nitric oxide in the regulation of electrical and contractive activity of unstriped muscles - I. V. Kovalyov; M. B. Baskakov; L. V. Kapilevich; M. A. Medvedev (Бюллетень сибирской медицины, 2004)
The aim of investigation is to reveal mechanisms being used by biological systems with the participation of nitric oxide NO in physiological processes and pathophysiological responses.The relative role of electro- and pharmacomechanical coupling of unstriped muscle cells (UMC) in mechanisms of nitric oxide action has been determined. It has been shown that activation of calcium ion input by biologically active substances had intensified NO relaxing effect. This activation has been mediated by potential-dependent and potential-insensitive intracellular mechanisms of calcium ion redistribution, the relative contribution of which had determined the direction of change in electrogenesis and contractions in the given particular type of unstriped muscle.It has been found that the potential-dependent nitric oxide impacts were connected with the suppression of calcium and/or natrium component of potassium UMC conductivity. As well as they were connected with the modulation of calcium-dependent and ATP-sensitive component of potassium UMC conductivity.Potential-independent NO control of unstriped muscle mechanic tension has been mediated, in many respects, by the modulation of UMC calcium signal system C-kinase branch, by the ratio of cyclic nucleotides concentrations (cGMP/cAMP) and by the directional mode of Na+-K+-2Cl–-co-transport. Myogenic effects of nitric oxide are determined by basal operation of protein kinase C in unstriped muscle cells.